2019
DOI: 10.1016/j.spinee.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A web-based platform to accommodate symptoms of anxiety and depression by featuring social interaction and animated information in patients undergoing lumbar spine fusion: a randomized clinical trial

Abstract: BACKGROUND: Approximately one-third of patients undergoing spine surgery have symptoms of anxiety and depression that correlate with pain, disability, and lower health-related quality of life. The use of web-based informative strategies before surgery and principles from cognitive behavioral therapy, have been applied in other patient groups, facilitating mobility and encouraging beneficial coping behavior. PURPOSE: To examine the effect of a web-based Spine Platform featuring Interaction and Information by An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 59 publications
0
59
0
Order By: Relevance
“…This study’s population comprises the patients enrolled and randomized from September 2015 to May 2017 [14] to an intervention group in a 2-arm RCT at a single-center orthopedic spine department in Denmark.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study’s population comprises the patients enrolled and randomized from September 2015 to May 2017 [14] to an intervention group in a 2-arm RCT at a single-center orthopedic spine department in Denmark.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these studies find a positive effect, when providing ISG, on patients’ depression, anxiety, or on quality of life [6-9], and it has been suggested that connecting with others on an ISG reduces the sense of isolation [10,11]. Other studies have mixed results or no positive results [12-14]. In addition, some studies even find negative results, as a Web-based survey suggests that the lack of actual physical proximity makes relationships developed within an ISG less meaningful and actually makes patients feel even more isolated [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search found 1,135 studies in the screening process. Among these, ten studies (Berget et al 2011 [ 28 ], Graven et al 2011 [ 29 ], Ammerman et al 2013 [ 30 ], Nagy et al 2017 [ 31 ], Chen et al 2019 [ 32 ], Strøm et al 2019 [ 33 ], Kern et al 2019 [ 34 ], Rogers et al 2014 [ 35 ], Cruwys et al 2014 [ 36 ], Croezen et al 2015 [ 37 ]) were assessed as eligible and were included in the analysis and synthesis ( Figure 1 ). Each study and its details after analysis have been shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis and synthesis of results, seven of the ten studies (Berget et al 2011 [ 28 ], Graven et al 2011 [ 29 ], Ammerman et al 2013 [ 30 ], Nagy et al 2017 [ 31 ], Chen et al 2019 [ 32 ], Strøm et al 2019 [ 33 ], Kern et al 2019 [ 34 ]) were at level I, while the other three studies (Rogers et al 2014 [ 35 ], Cruwys et al 2014 [ 36 ], Croezen et al 2015 [ 37 ]) were at level III of research levels of evidence. In ten studies, two studies (Berget et al 2011 [ 28 ], Rogers et al 2014 [ 35 ]) were obtained from occupational therapy literature, while the other eight studies were derived from nursing, psychology, and medicine and public health disciplines.…”
Section: Resultsmentioning
confidence: 99%